The effect of accounting disclosure on the implementation of investment decisions and its reflection on the investment reserve objectives – an exploratory study for investors in the Iraqi market for financial documents - سلطان, أياد شاكر; محمد, ريباز محمد حسين (Sulaimani Journal for Humanities, 2019)
The need to create relevance and transparency investment climate require fair disclosure of accounting information in the financial statements, which leads to rationalize investment decisions and reduce dangers associated with these decisions. The research aims to identify the extent of the commitment of corporations listed in the Iraqi Stock Market to the requirments of accounting diclosur and market instructions when preparing financial reports, and their impact on the rationalization of investment decisions, as well as to show the risks involved. To achieve the goals of the research and testing its hypothesis, a questionnaire was designed for this purpose. It was distributed to a sample of investors that deal with financial reports within the market, as well as using the techniques of (observation, inquiry and answer and field cohabitation that lead to accessing the information directly). The study found that investors in the Iraqi market realize the importance of accounting disclosure of accounting information in the rationalization of investment decisions , but it became clear that there are some shortcomings in the financial statements of the corporations listed on the Iraqi Stock Market resulting from non-compliance with the requirements of the accounting disclosure . The most important recommendations are the needs for corporations listed in the Iraqi Stock Market to submit their annual financial statements, both the actual and the planned statements for the coming year. The researchs calls to rewiew the existing laws to comply with laws of international markets, especially with regards to the commitment of corporations with international standards and accounting rules related to the accounting disclosure.